Respuesta :

Answer:

-1 13/56

Step-by-step explanation:

[tex] \frac{4}{5} \times ( - \frac{ 3}{7} ) - \frac{3}{8} + \frac{6}{5} \times ( - \frac{3}{7} ) = \\ = - \frac{12}{35} - \frac{3}{8} + \frac{6}{5} \times ( - \frac{3}{7} ) \\ = - \frac{12}{35} - \frac{3}{8} + ( - \frac{18}{35} ) \\ = - \frac{96}{280} - \frac{105}{280} - \frac{144}{280} \\ = - \frac{201}{280} - \frac{144}{280} \\ = \frac{345}{280} = - 1 \frac{65}{280} \\ = - 1 \frac{13}{56} [/tex]

#I_hope_this_helps

#save_earth

#stay_at_home

#keep_spirit